Pembelajaran Pendidikan Agama Islam di MI Ma’arif NU Langkap - Rokhimah, Rokhimah (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2022)
This study aims to describe the implementation of PAI learning at MI Ma'arif NU Langkap. This research is a qualitative descriptive study. The subjects of this study were madrasa heads, teachers, and students. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques use the Miles & Huberman model: data reduction, data presentation, and reasoning. The results showed that the form of PAI learning at MI Ma'arif NU Langkap was carried out in accordance with the procedural, normative and substantive stages. PAI learning is implemented by paying attention to the cognitive, affective, and psychomotor aspects of students. The management of PAI learning at MI Ma'arif NU Langkap is carried out using planning, implementation, and evaluation steps. The strategies used by teachers in teaching PAI atMI Ma'arif NU Langkap include team building strategies, direct learning engagement strategies, questioning strategies, collaborative strategies, peer teaching strategies, skills development strategies, and strategies for reviewing. The PAI learning process at MI Ma'arif NU Langkap uses a variety of methods, thus making learning more effective and the subject matter becomes more understandable to students, and Islamic values in PAI subjects can be internalized properly. Among these methods are the lecture method, the discussion method, the learning task method, the demonstration method, the question-and-answer method, the training method, the habituation method, the exemplary method, and the storytelling method.